2018
DOI: 10.1192/bjb.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

External validity and anchoring heuristics: application of DUNDRUM-1 to secure service gatekeeping in South Wales

Abstract: Aims and methodStructured clinical judgement tools provide scope for the standardisation of forensic service gatekeeping and also allow identification of heuristics in this decision process. The DUNDRUM-1 triage tool was completed retrospectively for 121 first-time referrals to forensic services in South Wales. Fifty were admitted to medium security, 49 to low security and 22 remained in open conditions.ResultsDUNDRUM-1 total scores differed appropriately between different levels of security. However, regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The DUNDRUM-1 assessment [44,45,[52][53][54][55][56][57] was used to measure need for the appropriate level of therapeutic security. The DUNDRUM-1 is a static measure completed prior to admission.…”
Section: Need For Therapeutic Security Risk Of Violencementioning
confidence: 99%
“…The DUNDRUM-1 assessment [44,45,[52][53][54][55][56][57] was used to measure need for the appropriate level of therapeutic security. The DUNDRUM-1 is a static measure completed prior to admission.…”
Section: Need For Therapeutic Security Risk Of Violencementioning
confidence: 99%
“…Our study using the DUNDRUM‐1 suggests that it may improve judgement about security needs and thereby not only contribute to safety but also treatment engagement and completion. It will also ensure consistency and transparency of decision‐making within a governance structure and is likely to fill a gap in clarity of criteria for offender‐patient allocation to levels of therapeutic security not only in Belgium, where they have been lacking (Jeandarme et al., 2019b), but also in other jurisdictions (Lawrence et al., 2018). It is suggested that the DUNDRUM‐1 Triage Security might be used as part of the pre‐admission assessment when admission to a mental health service or community mental health team is under consideration, and when assessing anyone referred for admission or transfer to a therapeutically secure service, to supplement other assessment tools and particularly those focusing on risk of harm to others.…”
Section: Discussionmentioning
confidence: 99%
“…9,[14][15][16][17] The DUNDRUM-1 triage security scale has been shown to have good internal consistency (Cronbach's alpha 0.95 in a Dundrum sample validation and 0.77 in an international validation study) and good interrater reliability. 9,10,[15][16][17][18][19] Interrater reliability is better following training. 17…”
Section: Needs Assessment Tool For Secure Carementioning
confidence: 99%